Javanese language learning assistance through digital media for teachers and students - Darihastining, Susi; Susilo, Jimat; Hidayat, Rahmad; Sulistyowati, Heny; Maisaroh, Siti; Chalimah, Chalimah; Faris, Ahmad (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2023)
In the millennial era, our students are already infatuated with digital. Javanese language which is included in the local content of Junior High Schools, students are presented with local languages which have shifted a lot in usage. Students rarely use Javanese which is difficult in the form of pronunciation. The problems are (1) students in reading, writing and speaking Javanese do not understand and find it difficult to apply aspects of pronunciation and phonetics in their use. (2) the lack of interest of millennial students in preserving regional languages. (3) based on observations, today's students are lacking, mastering Javanese is called